1999
DOI: 10.1111/j.1949-8594.1999.tb17505.x
|View full text |Cite
|
Sign up to set email alerts
|

Informal Science Experience, Attitudes, Future Interest in Science, and Gender of High‐Ability Students: An Exploratory Study

Abstract: The present study examined specific science-related attitudes, informal science-related experiences, future interest in science, and gender of young high-ability students. The sample consisted of 111 highability students between the ages of 9 and 13. Students completed the Test of Science Related Attitudes (TOSRA), the Science Experience Survey, and the Course Selection Sheet. Two regression models were developed to predict number of physical science and life science courses selected. In the first model, gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 23 publications
(30 reference statements)
0
23
0
2
Order By: Relevance
“…This is a major advantage that TOSRA has over some other science attitude tests which yield only a single overall score rather than a separate score for a number of distinct attitudinal measures. In addition to studies that have examined the validity of the TOSRA (Kalili 1987;Schibeci and McGaw 1981), the TOSRA has been used to evaluate innovations (Lott 2002), to compare the attitudes of different groups of students (White and Richardson 1993;Joyce and Farenga 1999) and to explore associations between the learning environment and students' attitudes (Fraser and Butts 1982;Fraser and Fisher 1982;Wong and Fraser 1996). For the purpose of our study, three of the seven scales were selected as being the most salient: Normality of Scientists, Attitude to Scientific Inquiry and Career Interest in Science.…”
Section: Methodsmentioning
confidence: 99%
“…This is a major advantage that TOSRA has over some other science attitude tests which yield only a single overall score rather than a separate score for a number of distinct attitudinal measures. In addition to studies that have examined the validity of the TOSRA (Kalili 1987;Schibeci and McGaw 1981), the TOSRA has been used to evaluate innovations (Lott 2002), to compare the attitudes of different groups of students (White and Richardson 1993;Joyce and Farenga 1999) and to explore associations between the learning environment and students' attitudes (Fraser and Butts 1982;Fraser and Fisher 1982;Wong and Fraser 1996). For the purpose of our study, three of the seven scales were selected as being the most salient: Normality of Scientists, Attitude to Scientific Inquiry and Career Interest in Science.…”
Section: Methodsmentioning
confidence: 99%
“…Past research suggests that few differences exist between primary school males and females in terms of attitudes toward science (Alexakos and Antoine 2003) and that gender differences are more likely to manifest themselves in the middle-school years (National Center for Education Statistics 2000), although perceptions toward science can begin developing before the age of 9 years (Joyce and Farenga 1999). Farenga and Joyce (1997a,b) reported that males were more likely to fix objects, build models, and seek action-oriented activities, as well as to listen to science news and read science books and magazines.…”
Section: Gender Issuesmentioning
confidence: 98%
“…The seven scales are called Social Implications of Science, Normality of Scientists, Attitude to Scientific Inquiry, Adoption of Scientific Attitudes, Enjoyment of Science Lessons, Leisure Interest in Science, and Career Interest in Science. The TOSRA has been widely used in science education research (e.g., Joyce & Farenga, 1999;Lang, Wong, & Fraser, 2005;Smist, Archambault, & Owen, 1994;White & Richardson, 1993).…”
Section: Introductionmentioning
confidence: 99%